2016
DOI: 10.1007/s00198-016-3792-3
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid and bone mineral density in postmenopausal osteoporotic women: the link lies within the fat

Abstract: In postmenopausal osteoporotic women, the strong univariable association between SUA levels and femur BMD is partly explained by the confounding effect of indices of adiposity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 49 publications
3
17
1
Order By: Relevance
“…Four cross-sectional studies from China reported a positive correlation between a higher sUA and greater BMD among postmenopausal women and older adults [ 19 – 22 ]. This conclusion was supported by other studies from Asia [ 23 25 ], as well as from the Netherlands and Italy [ 26 , 27 ]. However, other studies did not support this conclusion.…”
Section: Discussionsupporting
confidence: 80%
“…Four cross-sectional studies from China reported a positive correlation between a higher sUA and greater BMD among postmenopausal women and older adults [ 19 – 22 ]. This conclusion was supported by other studies from Asia [ 23 25 ], as well as from the Netherlands and Italy [ 26 , 27 ]. However, other studies did not support this conclusion.…”
Section: Discussionsupporting
confidence: 80%
“…However, whether the associations of uric acids with BMD are causal or independent of body fat is unclear yet. [27,[33][34][35] To our best knowledge, our study is the first to report the associations of uric acid precursors, hypoxanthine, and inosine with BMD status, [18][19][20][21][22][23] highlighting the importance of the purine metabolic pathway in bone metabolism.…”
Section: Discussionmentioning
confidence: 65%
“…Among 32 studies, 21 28 29 30 31 32 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 and 11 23 24 25 26 27 60 61 62 63 64 65 considered VIT D and SUA as the outcome, respectively. Within the 21 studies with VIT D outcome, 6 31 32 44 48 49 50 provided data of SUA and VIT D levels as continuous variables, 14 28 29 30 31 32 45 46 47 49 52 53 54 57 59 assessed association between SUA level as continuous data and categorical VIT D status, while 3 55 56 58 provided categorical data for both.…”
Section: Resultsmentioning
confidence: 99%
“…Most of them(23) were crosssectional studies. Their participants were either from the general population or had specific diseases, with mean age ranging from 36.9 to 76.9 years.Among 32 studies, 21[28][29][30][31][32][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] and 11[23][24][25][26][27][60][61][62][63][64][65] considered VIT D and SUA as the outcome, respectively. Within the 21 studies with VIT D outcome, 6[31,32,44,[48][49][50] provided data of SUA and VIT D levels as continuous variables, 14…”
mentioning
confidence: 99%